2014
DOI: 10.1108/tr-10-2013-0057
|View full text |Cite
|
Sign up to set email alerts
|

Loyalty program in Africa: risk-seeking and risk-averse adventurers

Abstract: Purpose – This article aims to test the relationship between expected attractiveness-satisfaction-loyalty for international adventure tourists visiting Tanzania. The proposed model is based on travel consumer behavior theoretical constructs extracted from the literature. Design/methodology/approach – This article aims to test the relationship between expected attractiveness-satisfaction-loyalty for international adventure tourists visiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…Specifically. Risk perception significantly influenced negative destination image, supporting previous studies ( Kozak et al, 2007 ; Mlozi, 2014 ; Kani et al, 2017 ; Nazir et al, 2021 ). Therefore, the greater a tourist’s risk perception, the more pronounced negative destination image, for example, when a tourist fears that an epidemic will affect the quality of tourism, this will reduce the enjoyment of the trip, or cause a change in travel plans during the trip.…”
Section: Discussionsupporting
confidence: 88%
“…Specifically. Risk perception significantly influenced negative destination image, supporting previous studies ( Kozak et al, 2007 ; Mlozi, 2014 ; Kani et al, 2017 ; Nazir et al, 2021 ). Therefore, the greater a tourist’s risk perception, the more pronounced negative destination image, for example, when a tourist fears that an epidemic will affect the quality of tourism, this will reduce the enjoyment of the trip, or cause a change in travel plans during the trip.…”
Section: Discussionsupporting
confidence: 88%
“…The results of H1 are following the research implemented by (Cheng et al, 2019); (Yunus & Rashid, 2016), it can be concluded that the better the service improvements provided by service providers include distributive justice, such as compensating service users with fair consideration between the two parties. The results of H2 are following the research implemented by (Breiby & Slåtten, 2018); (Mlozi, 2015); (Tan et al, 2017), it can be concluded that the more satisfied service users are using the services provided, it will have an impact on continuous use until loyal service users appear. The results of H3 are following the research implemented by (Nuns 2017;Sridhar & Ganesan, 2016;Velazquez et al, 2015), it can be concluded that the more happy service users are using the services provided, it will have an impact on spreading information positively by word of mouth.…”
Section: Hypothesis Testingmentioning
confidence: 83%
“…Usually, loyal service users tend to resist changes in service providers and still maintain services that are already satisfied. If the customer is satisfied with the services provided, the customer's intention to visit again will increase (Mlozi, 2015). Satisfaction will show an emotional reaction that is influenced by expectations that are following the interests of service users, whether it is following the level of service they want or vice versa, then this satisfaction will increase the intention to continue to buy back, always want to use the facilities that have been provided previously and provide recommendations for facilities that are available to use on others (Tan et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings also revealed that the tourists were concerned about a number of risks when they visited Tanzania. This means that if people perceive more risks, they will fear traveling to Tanzania in the future (Mlozi, 2014). In addition, they would not recommend the country to their friends and relatives.…”
Section: Mean and Standard Deviationmentioning
confidence: 99%